TERAPI SENI MENGGAMBAR SECARA KLINIS BERPENGARUH TERHADAP GANGGUAN EMOSI REMAJA DI SMPN 3 DEPOK, SLEMAN, YOGYAKARTA - Pradina, Nindithya Wahyu; Murdiyono, Wahyu Rochdiat; Muflih, Muflih Muflih (Coping: Community of Publishing in Nursing; Vol 4 No 2 (2016): Agustus 2016, 2016)
Since adolescents are in the period of searching for identity, puberty, and transition, they may experience emotional changes. Emotional changes can induce violence, concentration problems, and relationship problems with others. A preliminary study found out that nine adolescents had difficulty focusing on task completion, and eight had difficulty controlling their behavior. Art therapy is a nursing intervention to help adolescents express and control their emotions. This therapy is done using drawing therapy. This research was a quasi-experimental one with a pre-test and post-test equivalent control group design. A consecutive sampling method was used to collect the data from as many as 32 respondent. Asimple random sampling was used to divide the respondents into the two groups. Art therap yintervension was given over two weeks in six meetings in March 2016. The data were collected using questionnaires on January 24 and 26, 2015. The data were then analyzed using the bivariat analysis with the p value of > 0.05. The hypothesis testing indicates a p-value of 0.344 in the intervention group, and a p-value of 1.000 in the control group. The pre-test analysis in both groups indicates a p-value of 1.000, and the  post-test indicated a p-value of 0.285. There is an increase of 25% of the respondents who are emotionally stable in the intervention group, while 0% in the control group. There is no statistically significant influence of art therapy intervention on the emotional problems among adolescents at Public Junior High School 3, Depok Sleman, D.I.Yogyakarta. Yet, art therapy is clinically useful for emotion management. Key words: adolescent, art therapy, emotional problems,